2014
DOI: 10.1530/rep-13-0576
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytokine-suppressive anti-inflammatory drugs on inflammatory activation in ex vivo human and ovine fetal membranes

Abstract: Intrauterine infection and inflammation are responsible for the majority of early (!32 weeks) spontaneous preterm births (PTBs). Anti-inflammatory agents, delivered intra-amniotically together with antibiotics, may be an effective strategy for preventing PTB. In this study, the effects of four cytokine-suppressive anti-inflammatory drugs (CSAIDs: N-acetyl cysteine (NAC), SB239063, TPCA-1 and NEMO binding domain inhibitor (NBDI)) were assessed on human and ovine gestational membrane inflammation. Full-thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 39 publications
3
28
0
Order By: Relevance
“…This could be explained by the absence of iNOS in human trophoblast cells, as previously reported (51). In another study, the presence implicated as a valuable therapeutic approach for various conditions including cancer (73,74), chronic kidney disease (75), metabolic diseases (76), airway inflammatory disease (77), arthritis (78), and, in line with our findings in previous and current work, PTB (79). Interestingly, our data do not support any significant effect of DMA on the MAPK pathway.…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Asupporting
confidence: 90%
“…This could be explained by the absence of iNOS in human trophoblast cells, as previously reported (51). In another study, the presence implicated as a valuable therapeutic approach for various conditions including cancer (73,74), chronic kidney disease (75), metabolic diseases (76), airway inflammatory disease (77), arthritis (78), and, in line with our findings in previous and current work, PTB (79). Interestingly, our data do not support any significant effect of DMA on the MAPK pathway.…”
Section: Dma Inhibits the Transcriptional Activity Of Nf-κb But Not Asupporting
confidence: 90%
“…Thus, additional anti-inflammatory therapy may be needed to prevent PTB. We have recently demonstrated the significant suppressive effect of IA administration of polymyxin B (49) and cytokine-suppressive anti-inflammatory drugs (50) against intrauterine inflammation. In addition, Gravett et al re- ported significantly delayed age at birth and reduction in IA inflammatory cytokine/chemokine levels due to a combination of antibiotics, glucocorticoids, and nonsteroidal anti-inflammatory drugs (47).…”
Section: Discussionmentioning
confidence: 99%
“…Six replicate Transwells were established from each membrane and placed into six-well culture plates as previously described (Figure 1b). 20 The outer 'maternal' or decidual-facing compartment contained 3.5 ml supplemented media [DMEM/Ham's Nutrient Mixture F-12, phenol red-free, supplemented with 15 mM HEPES, pH 7.3 (Sigma Aldrich Pty Ltd, Castle Hill, NSW, Australia. ), 0.5% endotoxin/fatty acid-free BSA (Bovogen Biologicals Pty Ltd, East Keilor, VIC, Australia) and 4 mg/ml azithromycin (Pfizer, New York, NY, USA)].…”
Section: Human Extraplacental Membrane Transwell Modelmentioning
confidence: 99%
“…Shahin et al 18 found that the addition of N-acetyl cysteine (NAC), a free-radical scavenger and non-specific inhibitor of NF-kB and MAPK signalling, in conjunction with progestogen treatment for high-risk women with bacterial vaginosis in mid-pregnancy, greatly reduced the rates of PTB and neonatal morbidity/mortality. NAC has also been shown to prevent pro-inflammatory mediator production in vitro 19,20 and in vivo models of IUI. 21 NAC is not always well tolerated in pregnancy, 18,22 and alternate drugs with similar or improved effects are still being sought.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation